Impact of "Donkey", "Snap" dan "King" (DSK) non-digital gamification cards on fourth-grade students' math performance in fractions - Setambah, Mohd Afifi Bahurudin; Adnan, Mazlini; Zaini, Syaza Hazwani; Mujiasih, Mujiasih; Hidayat, Riyan; Ibrahim, Muhammad Alhaji; Hanazono, Hayato (Jurnal Infinity, 2024)
This research investigates the impact of Non-digital Gamification (NDG) techniques on students' math achievement, focusing on Fractions. Utilizing a quasi-experimental design, the study involved 100 primary school students in Perak. Two groups were formed: the control group, which followed traditional teaching methods, and the experimental group, which experienced NDG learning approaches. The findings indicate that students using NDG perform better in math (fractions) assessments compared to those using conventional methods. This study provides empirical evidence supporting the efficacy of NDG in teaching Fractions. The results underscore the potential for educators to innovate and enhance gamification tools, particularly in mathematics, contributing to educational advancements aligned with the goals of the Malaysian Ministry of Education.